Modification of inertial oscillations by the mesoscale eddy field (2010)
The modification of near?surface near?inertial oscillations (NIOs) by the geostrophic vorticity is studied globally from an observational standpoint. Surface drifter are used to estimate NIO characteristics. Despite its spatial resolution limits, altimetry is used to estimate the geostrophic vorticity. Three characteristics of NIOs are considered: the relative frequency shift with respect to the local inertial frequency; the near?inertial variance; and the inverse excess bandwidth, which is interpreted as a decay time scale. The geostrophic mesoscale flow shifts the frequency of NIOs by approximately half its vorticity. Equatorward of 30°N and S, this effect is added to a global pattern of blue shift of NIOs. While the global pattern of near?inertial variance is interpretable in terms of wind forcing, it is also observed that the geostrophic vorticity organizes the near?inertial variance; it is maximum for near zero values of the Laplacian of the vorticity and decreases for nonzero values, albeit not as much for positive as for negative values. Because the Laplacian of vorticity and vorticity are anticorrelated in the altimeter data set, overall, more near?inertial variance is found in anticyclonic vorticity regions than in cyclonic regions. While this is compatible with anticyclones trapping NIOs, the organization of near?inertial variance by the Laplacian of vorticity is also in very good agreement with previous theoretical and numerical predictions. The inverse bandwidth is a decreasing function of the gradient of vorticity, which acts like the gradient of planetary vorticity to increase the decay of NIOs from the ocean surface. Because the altimetry data set captures the largest vorticity gradients in energetic mesoscale regions, it is also observed that NIOs decay faster in large geostrophic eddy kinetic energy regions.